2020
DOI: 10.1001/jamadermatol.2020.1698
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Validation of Classification Criteria for Discoid Lupus Erythematosus

Abstract: IMPORTANCE Classification criteria are the standardized definitions that are used to enroll uniform cohorts for research studies. They emphasize high specificity and are distinct from diagnostic criteria. No universally recognized classification criteria currently exist for discoid lupus erythematosus (DLE), which has led to problematic heterogeneity in observational and interventional clinical studies across the field.OBJECTIVE To create and validate classification criteria for DLE using 12 previously defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“… 5 , 11 Trichoscopy exam should start with dry trichoscopy as using an immersion fluid hydrates the scale. Trichoscopy reveals thick arborizing vessels, follicular keratotic plugs, follicular red dots, peripilar scale, and peripilar erythema 5 , 11 , 17 ( Figure 2 ). Blue gray speckled dots and blue-white veil are two features observed in patients with Fitzpatrick skin type IV–VI.…”
Section: Types Of Le Alopeciamentioning
confidence: 99%
“… 5 , 11 Trichoscopy exam should start with dry trichoscopy as using an immersion fluid hydrates the scale. Trichoscopy reveals thick arborizing vessels, follicular keratotic plugs, follicular red dots, peripilar scale, and peripilar erythema 5 , 11 , 17 ( Figure 2 ). Blue gray speckled dots and blue-white veil are two features observed in patients with Fitzpatrick skin type IV–VI.…”
Section: Types Of Le Alopeciamentioning
confidence: 99%
“…Inclusion criteria were patients who met the following disease classification and/or inclusion terms for OLE, OLP, and other OLLs and were classified into the OLE, OLP, or control group. The diagnosis of OLE was made in patients presenting with typical discoid plaque based on the verified classification criteria for DLE and/or cases with oral lesions and positive lupus-associated serology (e.g., antinuclear antibodies, anti-double-stranded DNA, anti-Smith antibody) with or without systemic disease [32]. Patients who demonstrated classic white striae (reticulate pattern), erosive/ulcerative, or atrophic lesions with histology compatible with lichen planus according to the Modified World Health Organization criteria were classified as OLP [33].…”
Section: Methodsmentioning
confidence: 99%
“… 25% The whole layer of epidermis is necrotic, resulting in epidermal separation and a small amount of monocyte infiltration in the papillary layer of the dermis. DRESS [ 58 – 62 ] 2~6weeks Measles-like rash with small pustules and, in severe cases, erythroderma with extensive exfoliation of the skin, fever, enlarged lymph nodes, accompanied by fever and enlarged lymph nodes Eosinophilia, monocytosis, and thrombocytopenia Liver, kidney, lung, heart, lymph node, brain, eye, etc. 10% Keratinocyte necrosis, lymphocyte extravasation, surface sponge edema, interfacial vacuolar degeneration, dermal lymphocyte and eosinophil infiltration AGEP [ 65 69 ] 1~11days Joint, face, rash is aseptic pustule, less mucosal involvement, body temperature often >38 ℃ White blood cells and neutrophils are mostly elevated.…”
Section: Clinical Presentation Of Scarsmentioning
confidence: 99%
“…In addition to systemic complications, severe drug eruptions incorporating a large skin area can also produce severe sequelae. In a large retrospective cohort study [ 57 ], follow-up of adult patients with SJS/TEN revealed that nearly half of them had long-term sequelae, involving the eyes (corneal ulcers, cicatricial lesions, and shortening of the fornix and symblepharon), skin, gastrointestinal tract, genitals (erosion of genital mucosa may lead to vaginal adhesion), kidneys, lungs, and nails [ 58 ] (Fig. 2 ).…”
Section: Clinical Presentation Of Scarsmentioning
confidence: 99%